FROM THE RELIGIOUS STAGE TO THE POLITICAL STAGE: TEUNGKU DAYAH'S POLITICAL COMMUNICATION STUDY IN ACEH - Muntasir Muntasir; Muhammad Aminullah (al-Balagh : Jurnal Dakwah dan Komunikasi, 2020)
This paper describes the Teungku Dayah political communication model in maintaining the harmony of Muslims in Aceh. Political turmoil in society often creates unrest, as it separates religious and political values. On the other hand politics is actually very instrumental in the development of Islam in Aceh. Teungku Dayah is the main actor and key figure in political development in Aceh. As a public figure, Teungku Dayah has a stake in the mass vote in the regional elections, the president and other political contests. This research is an analysis of the phenomenon of Teungku Dayah's political role in maintaining the harmony of the people. The technique of data collection used was direct observation, and the data were analyzed by describing the actions of Teungku Dayah's political role. The research concludes that Teungku Dayah has its own system and character in guarding Aceh's political development. He uses the Islamic boarding school and the dayah institutionas media for political communication. But the shift in values in instant politics makes Teungku Dayah's political communication power limited to front stage politics. Further research is necessary on political communication in Teungku Dayah, since political communication is a dynamic study, as dynamic as the conditions in Aceh.